Quantum sensing with duplex qubits of silicon vacancy centers in SiC at room temperature - Kosuke Tahara; Shin-ichi Tamura; Haruko Toyama; Jotaro J. Nakane; Katsuhiro Kutsuki; Yuichi Yamazaki; Takeshi Ohshima (npj Quantum Information)
Abstract The silicon vacancy center in Silicon Carbide (SiC) provides an optically addressable qubit at room temperature in its spin- $$\frac{3}{2}$$ 3 2 electronic state. However, optical spin initialization and readout are less efficient compared to those of spin-1 systems, such as nitrogen-vacancy centers in diamond, under non-resonant optical excitation. Spin-dependent fluorescence exhibits contrast only between $$| m=± 3/2\left.\right\rangle$$ ∣ m = ± 3 / 2 and $$| m=± 1/2\left.\right\rangle$$ ∣ m = ± 1 / 2 states, and optical pumping does not create a population difference between $$| +1/2\left.\right\rangle$$ ∣ + 1 / 2 and $$| -1/2\left.\right\rangle$$ ∣ − 1 / 2 states. Thus, operating one qubit (e.g., $$\left\{| +3/2\left.\right\rangle ,| +1/2\left.\right\rangle \right\}$$ ∣ + 3 / 2 , ∣ + 1 / 2 states) leaves the population in the remaining state ( $$| -1/2\left.\right\rangle$$ ∣ − 1 / 2 ) unaffected, contributing to background in optical readout. To mitigate this problem, we propose a sensing scheme based on duplex qubit operation in the quartet, using microwave pulses with two resonant frequencies to simultaneously operate $$\left\{| +3/2\left.\right\rangle ,| +1/2\left.\right\rangle \right\}$$ ∣ + 3 / 2 , ∣ + 1 / 2 and $$\left\{| -1/2\left.\right\rangle ,| -3/2\left.\right\rangle \right\}$$ ∣ − 1 / 2 , ∣ − 3 / 2 . Experimental results demonstrate that this approach doubles signal contrast in optical readout and improves sensitivity in AC magnetometry compared to simplex operation.